PENGARUH KUALITAS PRODUK DAN SALES PROMOTION TERHADAP KEPUTUSAN PEMBELIAN HERBALIFE DI SIDOARJO - Salamah, Umi; Andayani, Sri; Maduwinarti, Ayun (Research Journal of Social Science and Economics, 2025)
A decision-making process carried out to determine the need for goods and services that need to be purchased and identify, evaluate and choose between alternative brands. The purchase decision occurs when someone is faced with several alternative choices to meet their needs. Many factors trigger purchasing decisions such as product quality and sales promotion. The purpose of this study was to determine the effect of product quality and sales promotion on Herbalife purchasing decisions in Sidoarjo. The sample of this study were Herbalife customers, knowing Herbalife and people who have consumed Herbalife products. the number of samples was 100 people. Questionnaire data collection techniques that are tested for validity and reliability. Data analysis techniques using assumption tests, multiple linear regression, t tests and F tests. The results of this study indicate that product quality has a significant effect on purchasing decisions and sales promotion has a positive and significant effect on purchasing decisions. Simultaneously, product quality and sales promotion affect Herbalife purchasing decisions in Sidoarjo by 77.4% of the purchasing decision variable can be explained. While other variables not used in this study explain 22.6 percent. t count> t table (11,648> 1,660) and a significance level of 0.000 <0.050. t count> t table (2,259> 1,660) and a significance level of 0.026 <0.050.